Natural Law and Global Bioethics - Tham, L.C., Joseph (Studia Bioethica, 2013)
This paper looks at the challenges of ethical behaviors in a global village. In some countries, the practices of medical tourism, organ trafficking, selective abortion based on gender, and lack of individual informed consent are seen as violations of universal human rights by international standards. Due to the general underdevelopment of local bioethical reflection, it is not uncommon for academics and governing ethical bodies to adopt wholesale secularized bioethical principles. Nonetheless, some scholars have raised the question of whether or not global ethics of universal human rights might not be neo-colonialism in disguise. How can the natural law tradition shed light on these challenges? The recent International Theological Commission document The Search for Universal Ethics: A New Look at Natural Law seeks to address the perennial problem of universality and particularism in ethics. It proposes rationality as the common ground to deduce the universal basis for human rights and dignity, thus avoiding the danger of consensus ethics prevalent in the secularized West on the one hand, and the danger of conflating multicultural and multi-religious settings with ethical relativism on the other. Lastly, the paper will look at the question of the incommensurability of ethical traditions with a look at the response of Alasdair MacIntyre. While shunning cultural relativism, he recommends mutual understanding of rival moral traditions through in-depth rational debates and encounters in order to arrive at the most valid moral system.